Transforming threats into opportunities: The role of human factors in enhancing cybersecurity - Silvia Colabianchi; Francesco Costantino; Fabio Nonino; Giulia Palombi (Journal of Innovation & Knowledge)
In today's fast-paced digital landscape, the importance of human factors in cybersecurity has become increasingly evident yet is often overlooked. This research employs the Delphi method to achieve expert consensus on the managerial actions that enhance cybersecurity by leveraging human factors. The study offers 16 key managerial actions, highlighting the shift from viewing humans as sources of vulnerability to acknowledging them as essential components of cybersecurity solutions. The findings suggest developing an organizational culture that values cybersecurity, delineating clear roles and responsibilities, and fostering continuous learning. This approach emphasizes the importance for organizations to recalibrate their cybersecurity strategies and provides a roadmap for implementing the suggested managerial actions. The study contributes to the socio-technical debate with a particular focus on human factors and provides practical guidance for organizations to improve their future cybersecurity posture.